2002
DOI: 10.1007/s00464-001-9225-0
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal esophageal acid exposure is common in morbidly obese patients and improves after a successful Lap-band system implantation

Abstract: There is a high prevalence of GERD in the obese population. Uncomplicated LAGB placement reduces the amount of acid in these patients with abnormal esophageal acid exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 11 publications
2
78
0
Order By: Relevance
“…When compared to healthy asymptomatic control subjects, 43 consecutive severely obese patients were found to have a lower LESP (11.9 ± 5.3 mmHg vs 15.9 ± 2.7 mmHg), and 51% were noted to have abnormal acid exposure [16] . Similarly, in a large cohort of patients with foregut symptoms, the prevalence of a mechanically defective LES (based on hypotensive LES, total length, or abdominal length) increased as BMI increased, with 55% of obese patients demonstrating a defective LES [17] .…”
Section: Pathophysiologymentioning
confidence: 92%
See 1 more Smart Citation
“…When compared to healthy asymptomatic control subjects, 43 consecutive severely obese patients were found to have a lower LESP (11.9 ± 5.3 mmHg vs 15.9 ± 2.7 mmHg), and 51% were noted to have abnormal acid exposure [16] . Similarly, in a large cohort of patients with foregut symptoms, the prevalence of a mechanically defective LES (based on hypotensive LES, total length, or abdominal length) increased as BMI increased, with 55% of obese patients demonstrating a defective LES [17] .…”
Section: Pathophysiologymentioning
confidence: 92%
“…The effects of LAGB on GERD are conflicting, however, with some studies demonstrating improvement in physiological GERD metrics [16] , while others show improvement on GERD questionnaires and/or through the discontinuation of GERD medications [50,51] . In contrast, several studies have demonstrated measured exacerbation of esophageal acid exposure, GERD symptoms, and the development or worsening of esophageal dysmotility following LAGB [52][53][54] .…”
Section: Lagb and Gerdmentioning
confidence: 99%
“…If medically indicated and if such a patient is willing, further bariatric surgery should be considered (EL B, C, D [229][230][231][232][233][234][235][236][237][238][239][240][241][242] ).…”
Section: Failed Treatmentmentioning
confidence: 99%
“…Whereas some studies report no differences between obese patients and a normal population [19][20][21][22], others have found a significantly lower LES pressure in obese patients [23,24]. However, most of these studies report LES pressure almost exclusively.…”
Section: Discussionmentioning
confidence: 83%